Multimodal Imaging in the Prenatal Diagnosis of Tuberous Sclerosis Complex. (2nd October 2012) - Gusman, Mariya; Servaes, Sabah; Feygin, Tamara; Degenhardt, Karl; Epelman, Monica
Abstract : Tuberous sclerosis complex (TSC) is an autosomal dominant disorder in which benign hamartomas develop in multiple organ systems. Increasingly, stigmata of the disease, such as cardiac rhabdomyomas, are detected on routine prenatal ultrasound. Such a finding should prompt additional imaging studies in order to confirm diagnosis and to identify potential complications, which vary greatly from patient to patient. Early diagnosis allows for accurate parental counseling, coordination of high-level perinatal care, and subspecialty followup. We present a case of TSC in utero wherein access to and use of multiple imaging modalities confirmed diagnosis and allowed the patient to receive optimal care prior to birth.